Gamifying Grammar: Enhancing Students’ Motivation Through Digital Game-Based Learning in EFL Classroom - Shofi Zuhri, Moh; Kavin Lidinillah, Moh; Nashihin, Muhammad (English Language Teaching Journal, 2025)
This study investigates the impact of digital-based gamification on students’ motivation and grammar comprehension in English as a Foreign Language (EFL) classroom. Grammar learning is often perceived as difficult and monotonous, which can reduce engagement and mastery. To address this challenge, Digital Game-Based Learning (DGBL) was implemented, integrating elements such as points, challenges, leaderboards, and instant feedback to create an interactive and motivating environment. A mixed-method design was employed, including pre-tests and post-tests to measure grammar comprehension, motivation questionnaires to assess engagement, semi-structured interviews to explore students’ perceptions, and classroom observations to monitor participation. Findings reveal that DGBL significantly improved both grammar understanding and student motivation. Students reported that gamified activities were enjoyable, challenging, and supported independent learning, while quantitative data indicated higher post-test scores and increased motivation levels. These results suggest that digital-based gamification can be an effective instructional strategy to enhance active participation, comprehension, and learner autonomy in EFL grammar instruction. However, careful consideration is needed to ensure equitable access to technology and alignment of game elements with learning objectives. Overall, the study highlights the potential of gamification to transform grammar learning into a more engaging and effective educational experience.